Science Learning in the Context of 'Indigenous Knowledge' for Sustainable Development - Rachid El Yazidi; Khaerul Rijal (International Journal of Ethnoscience and Technology in Education, 2024)
This study investigates the integration of Indigenous Knowledge (IK) into science education as a means to foster sustainable development among high school students. Through a qualitative descriptive approach, involving semi-structured interviews with 20 participants in Morocco, the research explores the impact of IK on enhancing students' understanding of local ecosystems, promoting interest in interdisciplinary studies, and contributing to cognitive and personal growth towards sustainable thinking. Findings indicate that incorporating IK into science curricula significantly enriches students' learning experiences by bridging the gap between traditional wisdom and scientific inquiry, thus making science education more relevant and engaging. This approach not only deepens students' appreciation for cultural diversity and environmental stewardship but also encourages a more holistic understanding of science and its application to global challenges such as climate change and biodiversity conservation. The study highlights the educational value of integrating IK in developing thinking and problem-solving skills, and a sense of global citizenship among students. It advocates for educational reforms that include IK as a vital component of science learning, suggesting that such integration can play a crucial role in achieving sustainable development goals by preparing students to engage thoughtfully with complex environmental and societal issues. This research contributes to the discourse on enhancing science education through the inclusion of diverse knowledge systems, offering insights into how such pedagogical innovations can support more sustainable and inclusive futures.